ANALISIS KUALITAS BAKTERIOLOGIS AIR MINUM ISI ULANG DI KELURAHAN SEMEMI, KECAMATAN BENOWO - Ria Ayu Dewanti; Lilis Sulistyorini (The Indonesian Journal of Public Health, 2017)
The high demand for drinking water consumption leading to increase public interest to consuming refilled drinking water, because it’s more practice, hygienic and affordable price. But still many Refilled Drinking Water Depots which not yet fulfilled conditions of drinking water quality which have beenspecified. This aims of this researchwas to analyze the bacteriological quality of raw water and refilled drinking water in the refilled drinking water depots and the incidence of diarrhea in Sememi village, Benowo district. This research was an analytical survey by cross-sectional design. Interview conducted on 100 respondents who are use bulkdrinking water using simple random sampling. Interviews were also to handlers in refilled drinking water depot. The observation included condition and the type of disinfectant were used, and taking water sample to laboratory for examination. The independentvariables were bacteriological quality of refilled drinking water, while the incidence of diarrhea most of the dependent variable. Another variable that also studied including duration of use and period storage of refilled drinking water. For the result, all samples of raw water showed growth of E. coli, afterprocessing 2 depots were not eligible. The prevalence of diarrhea in consumens was 16%. It is concluded that 11 of 16 (68.75%) diarrhea patients are consume eligible drinking water refills. Supervision to depots also important to prevent and reduce the incidence diarrhea from drinking water produced.Keywords: Refilled Drinking Water, Drinking Water Depot, diarrhea, E. coli